The complementary effect between biochar and ferrihydrite in sustainable Fenton-like oxidation of pollutant - Sen Guo; Cong Shen; Yao Gui; Huiming Li; Jinhong Lü; Jianfa Li (Journal of Saudi Chemical Society)
Biochar (BC) and ferrihydrite (Fh) were used together in activation of H2O2 for removal of sulfamethazine (SMZ), a refractory antibiotic pollutant. The results show a complementary effect between biochar and ferrihydrite on activation of H2O2, namely biochar accelerated Fe(Ⅲ)/Fe(Ⅱ) cycle through electron donation/transfer, while ferrihydrite enhanced the yield of •OH through a sustainable release of dissolved Fe. Thus several times more •OH was produced in the co-activated system (BC + Fh/H2O2) than either in the ferrihydrite-catalyzed Fenton-like system (Fh/H2O2) or in the biochar-activated system (BC/H2O2). Consequently, a more efficient oxidation of SMZ was observed in BC + Fh/H2O2, in which the reaction rate constant (kobs) is 30.7 times in Fh/H2O2 and 6.08 times in BC/H2O2, respectively. This research provides a simple and sustainable strategy for enhancing the efficiency of Fenton-like oxidation of pollutants.